Coexistence of Bartonella henselae and B. clarridgeiae in populations of cats and their fleas in Guatemala. Issue 2 (December 2015) - Bai, Ying; Rizzo, Maria Fernanda; Alvarez, Danilo; Moran, David; Peruski, Leonard F.; Kosoy, Michael
ABSTRACT: Cats and their fleas collected in Guatemala were investigated for the presence of Bartonella infections. Bartonella bacteria were cultured from 8.2% (13/159) of cats, and all cultures were identified as B. henselae . Molecular analysis allowed detection of Bartonella DNA in 33.8% (48/142) of cats and in 22.4% (34/152) of cat fleas using gltA, nuoG, and 16S–23S internal transcribed spacer targets. Two Bartonella species, B. henselae and B. clarridgeiae, were identified in cats and cat fleas by molecular analysis, with B. henselae being more common than B. clarridgeiae in the cats (68.1%; 32/47 vs 31.9%; 15/47). The nuoG was found to be less sensitive for detecting B. clarridgeiae compared with other molecular targets and could detect only two of the 15 B. clarridgeiae ‐infected cats. No significant differences were observed for prevalence between male and female cats and between different age groups. No evident association was observed between the presence of Bartonella species in cats and in their fleas.